2007
DOI: 10.3399/096016407782604820
|View full text |Cite
|
Sign up to set email alerts
|

Thou shalt versus thou shalt not: a meta-synthesis of GPs' attitudes to clinical practice guidelines

Abstract: Previous analyses of guidelines have focused on professional attitudes and organisational barriers to adherence. This synthesis suggests that the purpose of the guideline, whether its aims are prescriptive or proscriptive, may influence if and how guidelines are received and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
212
1
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(241 citation statements)
references
References 47 publications
16
212
1
12
Order By: Relevance
“…[39] The model of mixed evidence enables a holistic approach to evidence-based health care that contextualizes the biomedical data by also making sense of the social determinants of health which are critical when designing interventions for individuals leading complex lives. [40] This meta-synthesis clearly identifies the key challenges facing AF patients and healthcare professionals who manage their treatment, namely the importance of an early and accurate diagnosis, necessity of sufficient education pertaining to AF and available treatment, particularly OAC, and identification of patient barriers to treatment to improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[39] The model of mixed evidence enables a holistic approach to evidence-based health care that contextualizes the biomedical data by also making sense of the social determinants of health which are critical when designing interventions for individuals leading complex lives. [40] This meta-synthesis clearly identifies the key challenges facing AF patients and healthcare professionals who manage their treatment, namely the importance of an early and accurate diagnosis, necessity of sufficient education pertaining to AF and available treatment, particularly OAC, and identification of patient barriers to treatment to improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Carlsen and colleagues recently published a meta-synthesis of studies of GPs' attitudes to guidelines, and identified a number of barriers to implementation. 18 These include questioning of the guideline; the fact that patients are often more complicated than they appear in guidelines, and have their own views which can be impediments; fear of affecting the doctor-patient relationship; fear of 'missing a diagnosis' in guidelines that seek to limit investigations; time, skills, and resource limitations; and complex guidelines format. Most of these issues were not reflected in the current study; this may in part be a function of the PBL format prompting participants to consider these issues.…”
Section: Summary Of Main Findings and Comparison With Existing Literamentioning
confidence: 99%
“…Si bien algunas intervenciones son más efectivas que otras, se deben considerar múltiples elementos antes de decidir la estrategia de implementación más adecuada para un determinado contexto 33 . Es importante destacar, además, que numerosas publicaciones han resaltado el rol de las barreras y facilitadores tanto a nivel individual como organizacional para la implementación de las GPC [34][35][36][37][38] .…”
Section: Difusión Diseminación E Implementación De Gpcunclassified